Internalisasi Nilai Keberanian Berbasis Budaya Madura Untuk Mencegah Perilaku Perundungan Siswa di Sekolah Dasar - Firdaus, Yuliana Izdihar; Wahyuni, Esa Nur; Hambali, Muh (Jurnal Ilmiah Profesi Pendidikan, 2025)
The prevalence of bullying at SDIT ABFA Pamekasan indicates a lack of students’ understanding of cultural philosophies that can prevent such behavior. This study arises from the urgency of increasing bullying cases in elementary schools and the need for preventive approaches that are culturally grounded. The purpose of this research is to analyze students’ understanding of the value of courage based on Madurese culture, to examine the process of internalizing these values, and to identify their impact on both perpetrators and victims of bullying. This study employed a qualitative approach with a case study design. Data were collected through participatory observation, in-depth interviews with teachers, the principal, students, and parents, as well as documentation. The data were analyzed using Miles and Huberman’s interactive model, including data reduction, data display, and conclusion drawing. The validity of the data was ensured through triangulation of sources, techniques, and time. The results revealed that: (1) for perpetrators, courage based on Madurese culture is interpreted as a means to uphold self-respect and avoid humiliation; whereas for victims, courage means staying calm and not retaliating against the bully. (2) The internalization of courage values occurs through three stages: providing understanding, habituating positive attitudes, and applying them in daily life. This study contributes to bullying prevention efforts in elementary schools through a culturally rooted approach that strengthens students’ character based on Madurese values of courage.